Peningkatan Nilai Ekonomi dan Produktivitas UMKM Kue Basah Melalui Penyediaan Peralatan Produksi - Sirojuzilam Hasyim; Syarief Fauzie; Wahyu Sugeng Imam Soeparno; Sukma Hayati Hakim; Arif Rahman (Indo Publishing, 2025)
Amplas, a resident of Medan City, is an individual who makes selling traditional cakes her primary source of income. However, in running their business, they face various obstacles, particularly the limited production equipment, which is still traditional. The lack of supporting equipment such as baking pans, steamers, tampas, and stoves makes the production process longer and results in inconsistent results. This situation impacts production capacity limitations, unstable product quality, and difficulties in meeting increasing market demand. Furthermore, without adequate equipment, entrepreneurs face obstacles in developing more diverse and innovative product variations in line with market trends. To increase the economic value and productivity of their businesses, this program focuses on providing more modern production equipment. With the provision of baking pans, steamers, tampas, and stoves, it is hoped that production processes will run faster and produce better quality products. Furthermore, training on equipment use and maintenance will be provided so entrepreneurs can optimize their equipment and extend its lifespan. Through this program, it is hoped that wet cake MSMEs in Harjosari Village can improve the competitiveness of their products, develop more innovative cake variations, and expand their market reach. This will enable them to sustainably increase their income and economic well-being.